'I teach them that anything is possible'—exploring how adult leaders perceive and handle social factors of youth mental health in the context of young people's civic engagement. (29th April 2020) - Gotfredsen, Anne C; Landstedt, Evelina
Abstract: The aim of this qualitative study was 2-fold: to explore, in the context of young people's civic engagement in Sweden, (i) how adult leaders perceive social factors of youth mental health and (ii) how adult leaders handle such social factors within their organizations. Interviews were conducted with leaders engaged in various civic organizations that provide leisure activities for young people. Using thematic analysis, three themes were constructed. Firstly, the social landscape of youth mental health described how adult leaders perceived the social factors of youth mental health within the context of civic engagement. Secondly, the organizational structures developed by adult leaders illustrated the organizing forms that leaders created for young people's civic engagement. Thirdly, adult leaders' strategies for addressing the social factors of youth mental health reflected the strategies developed to handle e.g. stress and achievement pressure. The adult leaders recognized the importance of their organizations and their huge potential to have a positive impact on youth mental health. However, some participants also saw limitations in terms of their own resources and competence. They found themselves having to address the complex issue of social factors of youth mental health regardless of whether they felt competent and prepared to do this or not. Our findings contribute to the existing knowledge on youth and community development via the role of adult leaders in promoting young people's mental health by highlighting the organizational structures and leadership strategies developed by them.